2022
DOI: 10.1108/jeas-01-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of unemployment rate in developing economies: does banking system credit matter?

Abstract: PurposeIn developing countries, banks play a major role by acting as a conduit for the effective mobilization of funds from the surplus sectors of an economy for onward lending to the deficit sectors for productive investments that will in turn increase the level of employment and economic growth. There has being a rising trend in unemployment rate in Nigeria and South Africa and hence, the need for the study to assess the effectiveness of banking system credit in curbing unemployment rate by making a comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This finding is strengthened by Pagano & Pica (2011), Feldmann (2012), and Göçer, (2013 who respectively unraveled a similar impact during the investigation on 63 countries, 53 countries of the world, and 14 countries under the European Union. Azolibe et al (2022) found further the ability of banking system credit to control the unemployment rate in South Africa and Nigeria. At the same time, several studies have found the role of SMEs in creating employment, especially in developing countries (Abisuga-Oyekunle et al, 2020;Oyelana & Adu, 2015;Syed et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…This finding is strengthened by Pagano & Pica (2011), Feldmann (2012), and Göçer, (2013 who respectively unraveled a similar impact during the investigation on 63 countries, 53 countries of the world, and 14 countries under the European Union. Azolibe et al (2022) found further the ability of banking system credit to control the unemployment rate in South Africa and Nigeria. At the same time, several studies have found the role of SMEs in creating employment, especially in developing countries (Abisuga-Oyekunle et al, 2020;Oyelana & Adu, 2015;Syed et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Unemployment as a negative phenomenon is solved as a social problem by several scientific disciplines: economics, sociology, social pathology, social work or social policy and pedagogy (Achdut & Refaeli, 2020;Azolibe et al, 2022;Bennett & Ouazad, 2020). In 2019-2022, a new determinant -the COVID-19 pandemic -began to affect unemployment (Privara, 2022).…”
Section: Impacts Of the Covid-19 Pandemic On Unemploymentmentioning
confidence: 99%
“…This could reduce foreign investments sharply and significantly. Available literature suggests that higher unemployment rates result in lower intensity of FDI in host countries [30,[65][66][67]. For example, [67] investigated the main determinants of FDI in 16 African countries for the period 1991-2014, and they found that higher employment rates discourage FDI significantly.…”
Section: Foreign Direct Investment and Unemploymentmentioning
confidence: 99%